Strategic Alignment of Accounting, Taxes, and Digital Economy for Indonesia’s Economic Development - Widianingsih, Rini; Lukman, Lukman; Kinarsih, Siwi Rizki; Ludfiyani, Nurul; Dwiyantoro, Herdin; Muren, Louis Albertoaran; Kusumo, Damar Haryo (CARE: Journal Pengabdian Multi Disiplin, 2024)
This community service aims to provide a comprehensive understanding of integrated strategies in accounting, taxation, and the digital economy as an effort to face economic challenges in Indonesia. In the increasingly developing digital era, businesses and economic actors need to adapt to technology and understand dynamic tax regulations. This training is designed to help participants, especially those from the MSME sector and accounting professionals, integrate a strong understanding of accounting, compliance with tax regulations, and the application of digital technology in their business operations. Through a practical approach, participants will be invited to develop effective and efficient solutions to increase the competitiveness and stability of the national economy. The main focus of this training is to combine conventional accounting and taxation concepts with digital economic innovations, which are increasingly relevant in the industrial era 4.0. In addition, this training also discusses various tax challenges faced by businesses in the digital economy, such as e-commerce taxation, cross-border transactions, and evolving digital tax regulations. Participants will be taught how to utilize digital technology, such as cloud-based accounting software and tax applications, to facilitate more accurate and timely financial reporting and management.